Analysis of diversity, evenness and richness of vegetation in special purpose forest areas (KHDTK) at the University of Muhammadiyah Mataram - Gunadi, Putu Eka; Johari, Harry Irawan; Nurhayati, Nurhayati; Sukuryadi, Sukuryadi (Jurnal Agrotek Ummat, 2025)
The Special Purpose Forest Area of the University of Muhammadiyah Mataram has the potential to be a location for education and biodiversity conservation. This study aims to analyze diversity, species richness, and evenness of vegetation as indicators of forest ecosystem conditions. The study was conducted in June 2025 using a quantitative descriptive approach in 16 observation plots across four growth strata. The analysis was carried out using the Shannon-Wiener index for diversity, Margalef for species richness, and Pielou for evenness. The results showed that the tree stratum had a value of H' = 2.703, R = 5.951, and E = 0.780, reflecting a vegetation community with high and even diversity and distribution of individuals. In contrast, the seedling stratum showed very low values of H' = 0.049, R = 1.443, and E = 0.071, indicating the dominance of certain species and limited natural regeneration. Overall, 44 species from 24 families with a total of 236 individuals were identified. This pattern indicates an unbalanced vegetation structure across strata, with higher community stability at the tree level compared to younger growth levels. This finding provides a scientific basis for sustainable forest management and conservation planning.